Veterinary reproduction and obstetrics - Parkinson, Timothy J. (Saunders, 2009)
Covers normal reproduction and reproductive disorders and diseases in the common and less common domesticated species (llamas, alpacas, camels). This book includes the developments in reproductive biology and endocrinology, as well as the knowledge on the causes and treatment of reproductive disease